Developing Strong Teamwork to Support Excellence in Extension Programming - Hannah Carter; Amy Harder; Kevan Lamm (EDIS)
Sometimes differentiating a group from a team is difficult. Is the group of people that you work with truly a team? What benefits are there to being a member of a highly functioning team? In Patrick Lencioni’s iconic book on teamwork, The Five Dysfunctions of a Team, five elements are outlined as necessary for highly functioning teams. These are trust, ability to successfully engage in conflict, commitment to each other and the team, accountability, and focusing on collective results. This 2-page fact sheet was written by Hannah Carter, Amy Harder, and Kevan Lamm, and published by the UF Department of Agricultural Education and Communication, May 2013.